Lifetimes of Superdeformed States in 38 Ar - AUSTIN, ANNE ELIZABETH ROBY (My University, 2004)
Light nuclei provide an ideal laboratory for the study of the interplay between collective and single-particle interactions of nucleons. This thesis provides evidence via the lifetimes of states that the light nucleus 38 Ar undergoes superdeformation. Two highly deformed bands have been identified, one with a deformation parameter /32 = 0.30 ± 0.03. The deformation parameter of the more excited and more deformed band is less well measured, and it falls between /32 = 0.68 and /32 = 0.95. Superdeformation, the phenomenon in which a nucleus takes on an elongated shape with one axis approximately twice as long as another, occurs when nuclei are experiencing extreme conditions, particularly high angular momentum. The superdeformation of the nucleus 38 Ar is especially interesting because there is ample opportunity for interactions between superdeformed structures and normal deformed structures.
Keywords: Physics; Physics